Design Product Counting and Sorting Tools Using Esp8266-Based Volumenization - Taufik Marzuki; Akhmad Ahfas; Dwi Hadidjaja R.S; Izza Anshory (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Indonesia is a large country, so it does not rule out the possibility of natural resources owned by Indonesia such as natural resources coal, petroleum, gas, nickel and many others When we enter the industrial world, especially placed in the production process area, more precisely the process of sorting goods, it is very necessary to optimize the performance and results of the effectiveness of these working hours so as to get high performance efficiency and will get maximum yield. In the shipping section there are several occurrences of problems which include three main activities of the process of receiving, storing and sending when receiving or sending. We recommend reducing errors at the time of delivery of goods. As for the problem of empty packaging and calculating the number of inappropriate products, by providing solutions using loadcell sensors for weight, proximity sensors for automatic counters and using google sheets as data storage in real time using esp8266 as a controller module.causing performance effectiveness that is expected to be better automatically and using the sophistication of IoT systems connected to the web system.and supported by several Components include relays, pneumatics, googlesheets in order to get accurate results, product sorting tools using this loadcell will be compared with loadcell weighing devices that have been on the market in order to find out how accurately it has obtained the appropriate results using a volume of 103gr. The results of the entire test tool get accurate data ranging from googlesheet to reading through Lcd 20x4 testing is carried out five times so that this tool can be applied to other supporting tools.that the entire tool is able to answer the problems of the developing industrial world.